Complexos metálicos derivados de ligantes tripodais: Síntese, análise estrutural, aplicação como miméticos da atividade catalítica da superóxido dismutase e avaliação de citotoxidade frente à Caenorhabditis elegans in vivo. - Ebani, Patrícia Regina (2016)
The proposed dissertation presents the synthesis, characterization and mimetic application of complexes containing metals cations of the first transition series like CuII, NiII, MnII and FeIII. As starting materials have been used as only aminic precursor the tripodal ligand TREN tris(2-aminoethyl)amine followed by different compounds containing an aldehyde function, among then the biologic active shape of B6 vitamin, the pyridoxal, in hydrochloride. The ligands used in complexation rise by reaction of condensation among listed reagents, forming Schiff bases, which are much important in the coordination sphere of synthetized complexes. The metallic salts used on the synthesis have been used in hydrated perchlorate shape. The molecular formulas of synthetized complexes in this paper are C1[Cu(C21H24N4].(ClO4)2; C2[Cu(C24H27N7].(ClO4)2; C3[Cu(C21H26O3N4)(H2O)].(ClO4)2; C4[Cu4(C60H80N14O15(H2O)2].(ClO4).(H2O)2; C5[Cu(C15H22N2O2)].(ClO4); C6Ni(C22H30N6O4)].(H2O)7; C7[Mn(C30H38N7O6].(ClO4).(H2O) e C8[Fe(C30H36N7O6)].(H2O). Structural analysis of the eight synthetized complexes are recorded in solid state by xray diffraction on monocrystal. For superoxide dismutation tests (mimetic activity to SOD enzyme) was performed by measurements on the visible and ultraviolet region. Further, it has been conducted auxiliary analyses of characterization like cyclic voltammetry, infrared and UVVis spectroscopy, for all compounds. The cytotoxicity of the first three synthesized complexes were evaluated against the Caenorhabditis elegans in vivo.